2016
DOI: 10.1016/j.ijid.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the burden of pneumonia using administrative data from Malaysia, Indonesia, and the Philippines

Abstract: The burden of CAP and HAP is high. Results varied between the three countries, likely due to differences in socio-economic conditions, health system differences, and ICD-coding practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 36 publications
1
40
1
9
Order By: Relevance
“…CAP incidence in Japan in middle-aged adults (55--64 years) is 65/10,000 person-years, increasing markedly over age to 169 and 434/10,000 person-years in adults aged 65-74 years and 75--84 years, respectively. A recent study of three Asian countries [15] reported that CAP is responsible for 1424.5, 420.5 and 98.8 episodes per 10,000 discharges in the Philippines, Indonesia and Malaysia, respectively. In China, CAP incidence is estimated as 29.8-221.0 per 10,000 admissions including children [16].…”
Section: Cap Incidencementioning
confidence: 99%
“…CAP incidence in Japan in middle-aged adults (55--64 years) is 65/10,000 person-years, increasing markedly over age to 169 and 434/10,000 person-years in adults aged 65-74 years and 75--84 years, respectively. A recent study of three Asian countries [15] reported that CAP is responsible for 1424.5, 420.5 and 98.8 episodes per 10,000 discharges in the Philippines, Indonesia and Malaysia, respectively. In China, CAP incidence is estimated as 29.8-221.0 per 10,000 admissions including children [16].…”
Section: Cap Incidencementioning
confidence: 99%
“…Up-to-date data on the burden of disease is important for identifying individuals with unmet health needs, evaluating healthcare policies, and guiding evidence-based resource allocation decisions. The burden of pneumonia has been frequently reported in Western countries, but data are limited in Asia [9][10][11][12]. Previous research in Hong Kong has focused on the incidence of pneumonia in children under five years of age (published data current as of 2005) [13,14], the mortality trends from pneumonia [15,16], the emergence of resistant pathogens, pneumococcal serotype replacement, and the patient and environmental factors associated with pneumonia.…”
Section: Conclusion: Hospitalized Pneumonia Represents a Considerablmentioning
confidence: 99%
“…The incidence is clearly higher in older adults. Recent published estimates from others countries include 130.5 per 10 000 adults aged over 65 years in Malaysia, 25 172.4 cases per 10 000 for adults aged 85 and over in the Netherlands, 26 and 29.6 per 10 000 for all ages and 76.5 for adults aged 65 and over in Germany. 27 …”
Section: Introductionmentioning
confidence: 99%